Performance of barley varieties for malting quality parameters in north western plains of India - Kumar, Dinesh; Narwal, Sneh; Verma, RP S; Kumar, Vishnu; Kharub, A S; Sharma, Indu (Journal of Cereal Research, 2014)
Four barley cultivars were used to study the effect of cultivar and growing location on the grain and malt quality parameters. The results showed that both cultivar and growing location affect the quality parameters and two rowed cultivars have better grain and malt quality traits as compared to six rowed types. In two rowed type barley DWRUB-52 was found better and in six rowed type BH 902 was superior. It has also been observed that well irrigated and cooler regions like Karnal and Pantnagar are also suited to get better malt quality traits.